Building the Case for Localized Approaches to HIV: Structural Conditions and Health System Capacity to Address the HIV/AIDS Epidemic in Six US Cities - Panagiotoglou, D.; Olding, M.; Enns, B.; Feaster, D. J.; del Rio, C.; Metsch, L. R.; Granich, R. M.; Strathdee, S. A.; Marshall, B. D. L.; Golden, M. R.; Shoptaw, S.; Schackman, B. R.; et al. (AIDS and behavior, 2018)
Since the discovery of the secondary preventive benefits of antiretroviral therapy, national and international governing bodies have called for countries to reach 90% diagnosis, ART engagement and viral suppression among people living with HIV/AIDS. The US HIV epidemic is dispersed primarily across large urban centers, each with different underlying epidemiological and structural features. We selected six US cities, including Atlanta, Baltimore, Los Angeles, Miami, New York, and Seattle, with the objective of demonstrating the breadth of epidemiological and structural differences affecting the HIV/AIDS response across the US. We synthesized current and publicly-available surveillance, legal statutes, entitlement and discretionary funding, and service location data for each city. The vast differences we observed in each domain reinforce disparities in access to HIV treatment and prevention, and necessitate targeted, localized strategies to optimize the limited resources available for each city’s HIV/AIDS response.